The House of the Brazilian Woman: impacts of a cross-sectoral public health policy for abused women. (30th September 2020) - Almeida, J; Rocha, R; Signorelli, M; Silva, V; Prado, S; Evans, D
Abstract: Issue: Violence against women is a serious public health concern in Brazil; the country ranks 5th globally for femicide and has high rates of intimate partner violence. In response, a national policy created the House of the Brazilian Woman (HBW). HBWs aimed at caring for abused women, are staffed 24/7 with multi-disciplinary teams; cross-sectoral services include: psychosocial support; healthcare; specialized police; courts; public attorney's offices; temporary shelter; and access to financial support. Description of the Problem: The purpose of this study was to characterize the preliminary impacts of the HBW of Curitiba. Based on mixed-methods participatory action-research, data were collected between 2018-2020. We present quantitative measures describing the individuals served and a thematic analysis of in-depth interviews with HBW staff. Results: Since its opening, in 2016, the HBW of Curitiba has served around 50, 000 users, including women and perpetrators. The most prevalent type of violence reported was psychological (67%, n = 14, 343), followed by physical (25.8%, n = 5, 531), economic (5.2%, n = 1, 104) and sexual (2%, n = 428). Positive qualitative impacts perceived by staff were: 1) improved women's empowerment; 2) the importance of centralized resources; 3) acting as a support to ensure existing legal protections. The main challenges were: 1) high demand; 2) discontinuous care; 3) negative impacts on staff's health. Lessons: The HBW of Curitiba is a key cross-sectoral service for abused women, part of a greater national policy to prevent violence and support women. Despite serving a large number of women in a short period of time challenges remain including integration with other parts of the network and considerations of staff burnout. Key messages: Effective cross-sectoral policies for abused women are paramount for comprehensive women's health. Having cross-sectoral services in just one place operating 24/7 has high impact for abused women.